What makes a word so attractive? Disclosing the urge to read while bisecting. (22nd April 2018) - Girelli, Luisa; Previtali, Paola; Arduino, Lisa S.
Abstract : Expert readers have been repeatedly reported to misperceive the centre of visual stimuli, shifting systematically to the left the bisection of any lines ( pseudoneglect ) while showing a cross‐over effect while bisecting different types of orthographic strings (Arduino et al ., 2010, Neuropsychologia, 48, 2140). This difference has been attributed to asymmetrical allocation of attention that visuo‐verbal material receives when lexical access occurs (e.g., Fischer, 2004, Cognitive Brain Research, 4, 163). The aim of this study was to further examine which visual features guide recognition of potentially orthographic materials. To disentangle the role of orthography, heterogeneity, and visuo‐perceptual discreteness, we presented Italian unimpaired adults with four experiments exploiting the bisection paradigm. The results showed that a cross‐over effect emerges in most discrete strings, especially when their internal structure, that is being composed of heterogeneous elements, is suggestive of orthographically relevant material. Interestingly, the cross‐over effect systematically characterized the processing of letter strings (Experiment 2) and words (Experiments 3 and 4), whether visually discrete or not. Overall, this pattern of results suggests that neither discreteness nor heterogeneity per se are responsible for activating visual scanning mechanisms implied in text exploration, although both contribute to increasing the chance of a visual stimulus undergoing a perceptual analysis dedicated to pre‐lexical processing.